INFLUENCE OF ADVERTISING ON CONSUMER BUYING BEHAVIOUR FOR COSMETIC PRODUCTS - Dr. Vivek Kapre, (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Advertisements used by Forever Living to promote cosmetics products influences consumer buying behaviour by providing them with information about product benefits, price, quality, ingredients (materials of which the product is made of), quality, product quantity, product testimonial, product packaging, product name and product colour. The advertisements create awareness of the products and attracts more buyers.